Level of Ability to Pass Using the Inside of the Foot in Football - Ridwan, Andi; Bismar, Ahmad Rum (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
The purpose of this study was to determine the level of passing ability using the inside of the foot in football games. In this study, a quantitative approach was used with a descriptive research type that uses one variable without making comparisons with other variables. Descriptive research is research that is not intended to test a particular hypothesis but to describe or explain systematically, factually and accurately the facts and characteristics of a particular population. The population taken in this study were 306 students of Kumala State Elementary School, Makassar. The population that can represent students is 30 people, namely grades 5 and 6 obtained through random sampling techniques. The random sampling technique is a random sample selection that is intended as a representation of the total population. The data obtained are then analyzed and expressed in qualitative form with a percentage. Based on the results, the conclusion shows that the level of passing ability using the inside of the foot in football games of UPT SPF students of Kumala State Elementary School, Makassar is categorized as moderate.